2020
DOI: 10.1128/aem.02748-19
|View full text |Cite
|
Sign up to set email alerts
|

ESKAPE Bacteria and Extended-Spectrum-β-Lactamase-Producing Escherichia coli Isolated from Wastewater and Process Water from German Poultry Slaughterhouses

Abstract: The wastewater of livestock slaughterhouses is considered a source of antimicrobial-resistant bacteria with clinical relevance and may thus be important for their dissemination into the environment. To get an overview of their occurrence and characteristics, we investigated process water (n = 50) from delivery and unclean areas as well as wastewater (n = 32) from the in-house wastewater treatment plants (WWTPs) of two German poultry slaughterhouses (slaughterhouses S1 and S2). The samples were screened for ESK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 126 publications
(93 reference statements)
4
84
2
1
Order By: Relevance
“… K. pneumonia in environmental sources (10 studies) Wastewater from poultry slaughterhouses 51 ESBL-producing K. pneumoniae and Six colistin resistance Strains harbored bla SHV-1, 2, 25, 27, and 28, combinations SHV-2-TEM-1b and SHV-27-TEM-52b and CTX-M-1 were detected. Three strains with mcr -1 were isolated ND December 2016–September 2018 Savin et al 2020 [ 66 ] Water/sediment samples 9 MDR-ESBL producing strains Strains harbored bla SHV–28, bla CTX–M–15, tet (D), cat B3, aac (3)-IId, str A, str B, fos A, ere (A), sul 1, sul 2, oqx A, oqx B, aac (6′)Ib-cr, qnr S1, dfr A5 and dfr A14 Northern Germany 2017 Falgenhauer et al 2019 [ 65 ] Raw sewage one ESBL producing strain 182 (WGS of virulent phage PMBT1). Resistant patterns not determined ND Kiel ND Koberg et al 2017 [ 64 ] Washing machines, dishwashers ND β-Lactamase genes AmpC- and OXA-type were detected North-Rhine-Westphalia ND Rehberg et al 2017 [ 63 ] Wastewater treatment plants ND Colistin resistance, tetracycline resistance and erythromycin resistance Strains harbored mcr -1, tet M, erm B gene, ß-lactam ( bla CTX-M-32, ...…”
Section: Spatio-temporal Distribution Of K Pneumoniaementioning
confidence: 99%
“… K. pneumonia in environmental sources (10 studies) Wastewater from poultry slaughterhouses 51 ESBL-producing K. pneumoniae and Six colistin resistance Strains harbored bla SHV-1, 2, 25, 27, and 28, combinations SHV-2-TEM-1b and SHV-27-TEM-52b and CTX-M-1 were detected. Three strains with mcr -1 were isolated ND December 2016–September 2018 Savin et al 2020 [ 66 ] Water/sediment samples 9 MDR-ESBL producing strains Strains harbored bla SHV–28, bla CTX–M–15, tet (D), cat B3, aac (3)-IId, str A, str B, fos A, ere (A), sul 1, sul 2, oqx A, oqx B, aac (6′)Ib-cr, qnr S1, dfr A5 and dfr A14 Northern Germany 2017 Falgenhauer et al 2019 [ 65 ] Raw sewage one ESBL producing strain 182 (WGS of virulent phage PMBT1). Resistant patterns not determined ND Kiel ND Koberg et al 2017 [ 64 ] Washing machines, dishwashers ND β-Lactamase genes AmpC- and OXA-type were detected North-Rhine-Westphalia ND Rehberg et al 2017 [ 63 ] Wastewater treatment plants ND Colistin resistance, tetracycline resistance and erythromycin resistance Strains harbored mcr -1, tet M, erm B gene, ß-lactam ( bla CTX-M-32, ...…”
Section: Spatio-temporal Distribution Of K Pneumoniaementioning
confidence: 99%
“…The results showed that among these isolates, also were observed cases with multiple resistances. Savin et al (2020) reported that wastewater effluents from the poultry slaughterhouses exhibited clinically relevant bacteria (E. coli (39.4%), methicillin-resistant S.aureus (12.3%), K. pneumonia (10.8%), and species of the ACB (32.4%), which were widely distributed in their wastewater effluents (Savin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The wastewater from slaughterhouses is considered a relevant source of antimicrobial resistant bacteria and consequently may be important for its diffusion into the environment [ 46 ]. The livestock pressure in most of the Spanish rivers studied in this work was high, where pig farms stood out mainly ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the association between bla OXA-1 and resistance to aminoglycosides and quinolones reported by Osińska et al, 2016 [ 48 ] was confirmed in the present study, because the two WWTP isolates carrying bla OXA-1 were resistant to TO, LV, CIP, MXF and NOR. Indeed, the increased quinolone resistance rate in the isolates (50%) may be caused by the use of enrofloxacin in slaughtered broiler herds [ 46 ]. Furthermore, the high prevalence regarding AmpC β-lactamases could be related with the large number of Serratia and Citrobacter strains (carriers of chromosomal AmpC).…”
Section: Discussionmentioning
confidence: 99%